Robust Information Control Panel - Kumar Singh, Pawan; Prasad Pal, Ganesh; Kumar Tewari, Ravi; Saxena, Ankur (International Journal of Engineering and Technology, 2018)
The knowledge worker in today's digital enterprise utilizes multiple systems to perform day to day business activities. One of the most regularly performed tasks is to view the alerting and updates that occur across multiple systems. In a digital complex network that comprises several different systems, the knowledge worker ends up spending a significant amount of time in toggling across multiple systems to view the alerting. Apart from viewing alerting, the knowledge worker also performs many one-click tasks.A integrate view of information’s and alerting from multiple systems could help in saving the knowledge worker the burden of lap across multiple systems to view information while upgrading the overall knowledge worker experience and productivity levels.The Robust Information Control Panel intends to ease the life of a knowledge worker by providing view of the information from multiple systems. In addition to providing a personalized integrated view, the A Robust Information Control Panel also provides the ability to perform basic actions on information such as approvals thereby leading to increased knowledge worker productivity.